Analyses of association between PPAR gamma and EPHX1 polymorphisms and susceptibility to COPD in a Hungarian cohort, a case-control study - Dezso Balazs; Scholtz Beata; Csanky Eszter; Poliska Szilard; Penyige Andras; Schmelczer Ivan; Kilty Iain; Takacs Laszlo; Nagy Laszlo (BMC, 2010)
Abstract Background In addition to smoking, genetic predisposition is believed to play a major role in the pathogenesis of chronic obstructive pulmonary disease (COPD). Genetic association studies of new candidate genes in COPD may lead to improved understanding of the pathogenesis of the disease. Methods Two proposed casual single nucleotide polymorphisms (SNP) (rs1051740, rs2234922) in microsomal epoxide hydrolase (EPHX1) and three SNPs (rs1801282, rs1800571, rs3856806) in peroxisome proliferator-activated receptor gamma (PPARG), a new candidate gene, were genotyped in a case-control study (272 COPD patients and 301 controls subjects) in Hungary. Allele frequencies and genotype distributions were compared between the two cohorts and trend test was also used to evaluate association between SNPs and COPD. To estimate the strength of association, odds ratios (OR) (with 95% CI) were calculated and potential confounding variables were tested in logistic regression analysis. Association between haplotypes and COPD outcome was also assessed. Results The distribution of imputed EPHX1 phenotypes was significantly different between the COPD and the control group (P = 0.041), OR for the slow activity phenotype was 1.639 (95% CI = 1.08- 2.49; P = 0.021) in our study. In logistic regression analysis adjusted for both variants, also age and pack-year, the rare allele of His447His of PPARG showed significant association with COPD outcome (OR = 1.853, 95% CI = 1.09-3.14, P = 0.0218). In haplotype analysis the GC haplotype of PPARG (OR = 0.512, 95% CI = 0.27-0.96, P = 0.035) conferred reduced risk for COPD. Conclusions The "slow" activity-associated genotypes of EPHX1 were associated with increased risk of COPD. The minor His447His allele of PPARG significantly increased; and the haplotype containing the minor Pro12Ala and the major His447His polymorphisms of PPARG decreased the risk of COPD.